(-4x-2)+1/2(12x-22) simplify
1 answer:
Answer:
2x - 13
Step-by-step explanation:
Step 1 :
1
Simplify —
2
Equation at the end of step 1 :
1
(-4x - 2) + (— • (12x - 22))
2
Step 2 :
Pulling out like terms :
3.1 Pull out like factors :
12x - 22 = 2 • (6x - 11)
Step 3 :
Pulling out like terms :
3.1 Pull out like factors :
12x - 22 = 2 • (6x - 11)
Equation at the end of step 3 :
(-4x - 2) + (6x - 11)
You might be interested in
It should be E) none of the above because:
height = 0.5
Radius = 1
diameter = 2
Answer:
See below.
Step-by-step explanation:
So, we have:
![3pf^2-21p^2f+6pf-42p^2](https://tex.z-dn.net/?f=3pf%5E2-21p%5E2f%2B6pf-42p%5E2)
PART A:
Find the GCF. Notice that we have a 3 in every term and a p in every term. Thus, the GCF is 3p:
![3p(f^2-7pf+2f-14p)](https://tex.z-dn.net/?f=3p%28f%5E2-7pf%2B2f-14p%29)
This is the most we can do.
PART B:
Continue from where we left off. Factor the entire expression:
![3p(f^2-7pf+2f-14p)\\3p(f(f-7p)+2(f-7p))\\3p((f+2)(f-7p))](https://tex.z-dn.net/?f=3p%28f%5E2-7pf%2B2f-14p%29%5C%5C3p%28f%28f-7p%29%2B2%28f-7p%29%29%5C%5C3p%28%28f%2B2%29%28f-7p%29%29)
Answer:
4 passed 1 failed
Step-by-step explanation:
Answer:
t = 5
Step-by-step explanation:
It's asking what t needs to equal for the equation to be equivalent to -44.
-10t + 6 = -44
-10t = -50
t = 5
check
-10(5) + 6 = -44
-50 + 6 = -44
-44 = -44